Natural Degradation: Polymer Degradation under Different Conditions - Vetcher, Alexandre; Iordanskii, Alexey (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on some fundamental issues of polymers' natural degradation. It is mostly devoted to the different aspects of biodegradation, but some data on the action of water, oxygen, ozone, and UV/Vis light is also included. The consideration of the biodegradation in vivo as the superposition of decay and synthesis provides the opportunity for a fresh look at well-known processes.